VD_FINDINFO 2/2011/PBH vom 23. Dezember 2010 - VD Tribunal cantonal (2010)
RÉCUSATION, EXPERT-ARBITRE, JUGE ARBITRE, TRIBUNAL ARBITRAL DU SPORT | 1 al. 1 C-Arb, 20 C-Arb, 3 C-Arb, 3 let. b C-Arb, 45 al. 1 C-Arb, 45 C-Arb, 346 CPC, 427 let. b CPC